2018
DOI: 10.1111/dar.12814
|View full text |Cite
|
Sign up to set email alerts
|

Highly deficient alcohol health warning labels in a high‐income country with a voluntary system

Abstract: Voluntary recommendations in NZ appear to have been inadequate for producing health warnings on alcoholic beverage containers that are consistent with evidence-informed recommendations for effective labels. This finding suggests that mandatory standardised labelling outlining alcohol-related risks may be required to ensure adequate consumer information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Research has also indicated variation in what type of messages the alcohol industry is willing to support. Tinawi et al [ 150 ] examined a sample of 59 low-cost local and imported beers, wines and ready-to-drink alcoholic beverages available in New Zealand in 2016–2017, where warning labels are voluntary. They noted that 80% had pregnancy-related warnings, 73% had industry-led warnings, e.g., “responsible” consumption, and 19% had warnings about drink driving or heavy machinery.…”
Section: Resultsmentioning
confidence: 99%
“…Research has also indicated variation in what type of messages the alcohol industry is willing to support. Tinawi et al [ 150 ] examined a sample of 59 low-cost local and imported beers, wines and ready-to-drink alcoholic beverages available in New Zealand in 2016–2017, where warning labels are voluntary. They noted that 80% had pregnancy-related warnings, 73% had industry-led warnings, e.g., “responsible” consumption, and 19% had warnings about drink driving or heavy machinery.…”
Section: Resultsmentioning
confidence: 99%
“…ingredients, calories, warnings) self-regulated by alcohol companies. Tinawi et al [51] argue that voluntary warnings on alcohol packaging in New Zealand, like the UK, are inadequately designed to inform consumers and that evidence-based, standardised requirements outlining alcohol-related risks are necessary. As over 740 000 of all new cancer cases in 2020 globally were attributable to alcohol consumption [52], with alcoholic liver deaths in the UK increasing [53], our findings could help inform packaging regulations to meaningfully inform consumers about alcoholic products and potential harms.…”
Section: Discussionmentioning
confidence: 99%
“…Despite international public health calls [ 16 , 40 ] and specific World Health Organization recommendations for widespread provision of nutrition information on packaged alcoholic products to guide informed consumer choice [ 41 ], energy labelling (i.e., the listing of calorie/kilojoule information) is not mandatory in many jurisdictions, including the United States, European Union, and Australia. Reports suggest international alcohol industry pressure has delayed more widespread uptake in international policy (e.g., the Codex Alimentarius) of labelling requirements supported by public health evidence [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reports suggest international alcohol industry pressure has delayed more widespread uptake in international policy (e.g., the Codex Alimentarius) of labelling requirements supported by public health evidence [ 42 ]. Voluntary industry uptake of such labelling has been limited to date; 5.1% of alcoholic beverage containers showed nutritional data including energy information in a recent New Zealand audit [ 40 ], and earlier in England only 1.3% showed energy information [ 43 ]. Despite this, studies show strong public support for alcohol nutrition and energy labels, including among drinkers.…”
Section: Discussionmentioning
confidence: 99%